Unlearning Protestantism : sustaining Christian community in an unstable age - Schlabach, Gerald (Grand Rapids, Mich. : Brazos Press, 2010)
"This book is not about encouraging people to abandon Protestant churches. It is not a pamphlet to persuade Protestants to become Roman Catholic. Rather it is about virtues that all Christian communities need to sustain their communal lives, whatever their ecclesial location"--Introduction.
The Protestant dilemma -- The matter of continuity -- The practice of stability -- Stability writ large -- Stability in hard times : loyal dissent -- Giving the gift of stability to a globalizing world.
Includes bibliographical references (pages 255-265) and index.
Keywords: Church controversies; Continuity of the church; Catholic Church -- Discipline; Church controversies -- Mennonites